The AN EXAMINATION OF THE ROLE OF TOURISM TO ELIMINATE POVERTY - Ashish Sharma , Kuldeep Kaur (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Tourists' influence on absolute poverty in two developing countries is examined in this study, which goes beyond the economic impact. People in poverty are evaluated to discover if tourist spending has an impact. An error correction model may be used to estimate the link between poverty and tourism spending. A favourable effect on the poor from visitors does tend to be shortlived, however, as the poor at lower economic levels are more directly affected by tourism growth. Studies in developing nation’s show that the effects of tourism development vary, and this means that the policy implications vary as well